Experiences of ethnic minority students in a culturally diverse school - Haryana, Lia; Widiati, Utami (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2021)
Being ethnic minority students in a culturally diverse school is a challenge. This study aims to explore the experiences of students from various ethnic groups as ethnic minority students in a culturally diverse school. These experiences cover both the barriers and the success of those students in adjusting to the culturally diverse school. Five students coming from diverse ethnic groups were recruited as the participants. This study adopted a qualitative design by using a semi-structured interview as the research instrument. The interview data were transcribed and then coded into several themes based on the focus of the research. The results showed that the ethnic minority students might find difficulties adjusting to the school at first. However, they gradually adjusted to the school because of these following factors: teachers’ support, students’ cohesiveness, students’ cooperation, and teachers’ equity. The results of this study imply that the ethnic minority students once experienced some challenges in adjusting to the school environment before they were facilitated with more positive schooling experiences related to student-student relationships and student-teacher relationships. Menjadi siswa etnis minoritas di sekolah dengan beragam budaya merupakan sebuah tantangan. Penelitian ini bertujuan untuk menggali pengalaman siswa dari berbagai latar belakang etnis sebagai etnis minoritas di sekolah yang beragam budaya. Pengalaman-pengalaman ini meliputi hambatan maupun keberhasilan para siswa tersebut dalam menyesuaikan diri dengan sekolah yang beragam budaya. Lima siswa yang berasal dari kelompok etnis yang berbeda direkrut sebagai responden. Penelitian ini menggunakan desain kualitatif dengan menggunakan wawancara semi terstruktur sebagai instrumen penelitian. Data hasil wawancara ditranskripsikan kemudian dikategorikan menjadi beberapa tema sesuai dengan fokus penelitian. Hasil penelitian menunjukkan bahwa siswa etnis minoritas pada awalnya kesulitan menyesuaikan diri dengan lingkungan sekolah. Namun, lambat laun mereka bisa menyesuaikan diri dengan sekolah karena beberapa faktor, yaitu dukungan dari guru, kekompakan siswa, kerjasama siswa, dan perlakuan yang imbang dari guru. Hasil penelitian ini mengimplikasikan bahwa siswa etnis minoritas mengalami beberapa tantangan dalam menyesuaikan diri dengan lingkungan sekolah sebelum mereka difasilitasi dengan pengalaman sekolah yang lebih positif yang berkaitan dengan hubungan antara siswa-siswa dan hubungan siswa-guru.